Uncertainty and Territorial Innovations in Peri-urban Agricultural Spaces - Laurens, Lucette (Journal for Geography, 2009)
Linking uncertainty and territorial innovations advances the understanding of processes and dynamics in peri-urban agricultural spaces, which seem contradictory at first glance, caught between mechanisms of appropriation related to different uses and abandonment due to the decline of agricultural activities. This inquiry allows us to use this paradox as a stimulating perspective for investigation. Examples from Languedoc-Roussillon and the Montpellier agglomeration illustrate these processes of socio-spatial restructuring, in which agricultural spaces are confronted with new, uncertain, and innovative dynamics. Therefore, these spaces appear to be multifunctional spaces to be invented. They could occupy a new place in structuring urbanity on the scale of current agglomerations.